Optimized Permanent Magnet Assisted Synchronous Reluctance Motor Design and Comparison (PMa-SynRM) Induction Motor with Identical NEMA Stator Frame - Vorezky; Solly Aryza; Hamdani (INFOKUM, 2021)
The performance of a synchronous reluctance motor (SynRM) depends on the direct axis inductance (Ld) and the square axis inductance (Ld) of the machine. To achieve a high torque density and power factor, increasing the saliency ratio Ld/Lq and making this inductance difference (Ld-Lq) large enough is a well-known method. Otherwise, the performance of the motor will remain below that of a similar induction engine using a similar stator. This study attempts to place the right amount of permanent magnet in the rotor in the right position, it will be possible to achieve a significant increase in the performance of permanent magnet-assisted SynRM (PMa-SynRM) which will be comparable to an induction machine with the same stator. The PMa-SynRM will benefit from the reduction in price due to the use of a conventional induction machine stator.